PENGARUH PERTUMBUHAN EKONOMI (PDRB), PENDAPATAN ASLI DAERAH (PAD) DAN DANA ALOKASI UMUM (DAU) TERHADAP BELANJA DAERAH DI KABUPATEN PASAMAN BARAT (Studi Kasus Pada Pemerintahan Kabupaten Pasaman Barat Tahun Anggaran 2005-2012) - Wulandari, Fitria; Asrizal, Asrizal; Jolianis, Jolianis (Pendidikan Ekonomi, 2013)
ABSTRACT  FitriaWulandari. 09090052. Effect of Economic Growth (GDP), Revenue (PAD) and the General Allocation Fund (DAU) of the Government Expenditure In West Pasaman. Thesis. Economic Studies Program STKIP PGRI West Sumatra. Padang. 2013. Local Government to allocate funds in the budget Expenditure in the budget to increase the fixed assets. Expenditure allocation is based on local needs for facilities and infrastructure, both for the convenience of the government and pablik facilities. This study aims to analyze : (1) Effect of Economic Growth on Local Spending, (2) Effect of local revenue (PAD) of the Shopping Area, (3) Effect of the General Allocation Fund (DAU) to Regional Shopping, (4) Economic Growth, Revenue, General Allocation Fund simultaneously on Government Expenditure In West Pasaman . Types of research used in this study is a quantitative approach. Object of research conducted in the West Pasaman. The data used are time series data year budget period 2005-2012 obtained from BPKAD and BPS. The variables tested were the Economic Growth GDP seen from the data (X1), Revenue (X2), the General Allocation Fund ( X3 ) as the independent variable and Expenditure ( Y ) as the dependent variable. The data will be analyzed through the classical assumption. While used to test the hypothesis significance testing and multiple linear regression analysis. This study found that : (1) Economic Growth significant effect on regional expenditure, (2) Revenue Expenditure bepengaruh significant, (3) General Allocation Funds significant effect on regional expenditure, and simultaneous hypothesis testing (4) Economic Growth, Revenue and General Allocation Funds significant effect on regional expenditure .